Return on character the real reason leaders and their companies win - Kiel, Fred (Harvard Business Review Press, 2015)
"In 2001, Jim Collins published research findings that identified the "blend of personal humility and professional will" that enabled the Level 5 Leader to drive an otherwise unremarkable organization to greatness. Now, in Return on Character, Fred Kiel offers us the findings of a new study that tell us how to grow and develop that kind of extraordinary leadership. This groundbreaking book is based on Kiel's seven years of rigorous research into the "black box" that contains the little understood connection between character, leadership excellence, and organizational results. Grounded by nearly 9,000 employee observations on CEOs and their teams, Kiel offers solid evidence that character matters-leaders of strong character in his study achieved up to five times the ROA for their organizations than did leaders of weak character. Most people want to believe that good character wins, but many hard-nosed executives and analysts are skeptical on that point.